Facts on domestic waste and industrial pollutants - Johnstone, Hugh. (New York : F. Watts, 1990)
Examines the growing problem of waste disposal and alternatives to such methods as landfills and garbage dumps.
Keywords: Refuse and refuse disposal -- Juvenile literature; Refuse and refuse disposal